Christian Boltanski. Petite mémoire de l’oubli - Gaëlle Périot-Bled (Images Re-Vues)
From everyday objects collection, exhibited in showcases, to monumental setups, Christian Boltanski is obsessed with saving humanity from oblivion. Collection and archiving are this artist's main obsessions, as if collecting objects and photographies could ward off the inoxerable loss one experiments in time. His work aims at creating a mankind museum, but a vitalized museum, with devices that integrate the audience, and leads one to be an active part of the setup. In time and place of its exhibition, every setup is a play that happens thanks to the audience and then goes back to nothingness, yet surviving in one's affective memory. We would like to return to the shapes that take this paradoxical work of memory, constantly reminding us that we forget.